TO EVALUATE HEPATOPROTECTIVE ACTIVITY OF LEAVES OF OCIMUM SANCTUM USING ANIMAL MODEL - Jain, Anurag (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: To evaluate the hepatoprotective activity of leaves of Ocimum sanctum in carbon tetrachloride (CCl4) induced hepatotoxicity in albino rabbits. Methods: This study was conducted on 12 healthy albino rabbits of either sex weighing 1.5-2.0 kg, divided into 2 groups. Hepatotoxicity was induced in rabbits by CCl4 0.05 mg/kg, intra-peritonealy. Alcoholic extracts of leaves of O. sanctum was administered orally for 20 days from 1 day to day 20 in the doses of 100 mg/kg/day with the help of a syringe. Results: Group I: The rise of serum transaminase (p<0.001), serum alkaline phosphatase (p<0.001), serum bilirubin (p<0.001) and decrease in serum albumin (p<0.001) due to hepatotoxic effect of CCl4 when compared to zero-day of same group (p<0.001). Group II: O. sanctum extract was able to bring down the level of serum transaminase, serum alkaline phosphatase, serum bilirubin and increased in serum albumin in a statistical highly significant amount (p<0.001), when compared with Group I. Conclusion: O. sanctum leaves found to be effective in reducing serum glutamic oxalacetic transaminase, serum glutamic pyruvic transaminase alkaline phosphatase, serum bilirubin. O. sanctum extract helps in normalize serum albumin level. O. sanctum extract had shown protection in the restoration of liver function and regeneration of liver cells as observed on histopathology.